(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article discusses one of the important issues in teaching 8th-grade students about oxides in the subject of chemistry, which is environmental safety and the concept of a green economy. The use of elements of a green economy and environmental awareness in explaining the properties of oxides in chemistry classes is an integral part of modern education. This approach teaches students to live in harmony with nature, use resources properly, and feel responsible for the environment.